2011
DOI: 10.2174/1874210601105010154
|View full text |Cite
|
Sign up to set email alerts
|

Self Reported Halitosis in Relation to Glycated Hemoglobin Level in Diabetic Patients

Abstract: Objective:This study was conducted to examine the relationship between the glycated hemoglobin level (HbA1c) and halitosis status among diabetic patients affected with periodontitis and to examine if there is a relationship between halitosis and different periodontal parameters. Methods and Materials:Consecutive type 2 diabetic patients were recruited from patients presented for treatment at a University hospital. Age, gender and smoking were recorded. A structured questionnaire on patients’ perception of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
1
24
1
1
Order By: Relevance
“…28 An association between an increased level of HbA1c with the presence of halitosis has been described. 12 Some authors have suggested breath acetone as a biomarker of poor metabolic control in children with diabetes, 11,12 since ketonic bodies are increased in uncontrolled patients. Our study corroborates the literature, as breath acetone and xerostomia were significantly increased in the uncontrolled children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 An association between an increased level of HbA1c with the presence of halitosis has been described. 12 Some authors have suggested breath acetone as a biomarker of poor metabolic control in children with diabetes, 11,12 since ketonic bodies are increased in uncontrolled patients. Our study corroborates the literature, as breath acetone and xerostomia were significantly increased in the uncontrolled children.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4 Regarding the oral manifestation of type 1 diabetes, the association between periodontal disease and diabetes is already well established in adults, [5][6][7][8][9] as well as the incidence of xerostomia 10 and breath acetone. 11,12 Diabetes-related parameters have been linked to periodontal problems in children 5,6,13 and also accelerated tooth eruption. 14 On the other hand, it is still controversial whether these parameters are associated with dental caries [15][16][17][18][19] and oral manifestations, such as geographic and coated tongue.…”
Section: Palavrasmentioning
confidence: 99%
“…Certain diseases, such as diabetes and uremia, and medications could also contribute to bad breath. [59][60][61] Halitosis affects to various degrees key aspects of person's quality of life refl ecting in social relationships and emotional well-being. Treatment of halitosis is achievable once its etiology is properly diagnosed.…”
Section: Probiotics and Halitosismentioning
confidence: 99%
“…Genuine halitosis as opposed to pseudohalitosis must be assessed. In the case of genuine halitosis, evaluation should include a detailed history of oral malodor, triggers, duration, aggravating, and relieving factors (Akos et al 2012;Al-Zahrani et al 2011).…”
Section: History and Evaluationmentioning
confidence: 99%